Argumentative structure and persuasive discourse strategies in the Malaysian secondary school english debate finals - Balakrishnan, Ganeish (2019)
Academic debate in schools and higher learning institutions is a formal activity that helps develop students’ speaking skills and refine their argumentative skills. In order to debate effectively, debaters must understand the fundamental characteristics of a debate especially in relation to the use of persuasive language and master the techniques for structuring arguments. The aim of this study is to examine persuasive discourse in Malaysian school debates with regard to argumentative structure, persuasive discourse strategies and the combination of both to affect persuasion. The findings of the study are expected to make preparation and planning for debate more effective. This research design is qualitative using the case study approach. The data collection of this study involves a video recording of the National Level Secondary Schools Debate Finals 2012. The video recording of the debate finals was subjected to discourse analysis. Three models were used for the analysis of the data. The first model, Toulmin’s (2003) Argumentative Structure, was used to analyze the structure of the arguments. The second model, Johnstone’s (2012) persuasive discourse strategies, was used to analyze the discourse strategies used in the debate. Aristotle’s modes of persuasion (ethos, pathos and logos) (in Cockcroft, 2005) were used to examine the modes for persuasion used in the structure of the arguments and in the persuasive discourse strategies. The findings show that there are notable differences between the two debating teams with regard to argumentative structure. The government team (the winning team) had at minimum four elements out of six required in the argumentative structure compared to the opposition team that had a minimum of three elements. The number and type of elements in the argumentative structure determines the relative strength of the arguments. The argumentative structure used by both the teams reflected the logic reasoning (logos) of the arguments. The findings also show a significant presence of persuasive discourse strategies to achieve persuasion. Persuasive discourse strategies appeared three times more in the arguments of the government team in comparison to the opposition team. The three strategies present were quasilogical, presentational and analogical, with the presentational strategy being the most salient feature. All three strategies evoked the pathos appeal of persuasion. The findings show that the use of both, argumentative structure and persuasive discourse strategies result in the application of logos and pathos, making persuasion work more effectively in school debates.